Analisis Peran Komunikasi Politik dalam Pencitraan Calon Pemimpin pada Kontestan Pemilu - Setiawan, Muh. Farhan; Yanto, La Yuki; Nurfiani, Nurfiani; Astuti, Fina; Rahmatia, Rahmatia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Political communication has an important role in shaping the image strategy of potential leaders in the eyes of the public. Appropriate political branding is aimed at increasing electability through forming positive public opinion towards candidates. This research aims to analyze which message designs and political communication channels are most effective in building a strong reputation and image for a potential leader. A literature study was carried out on several references related to political communication strategies in relation to candidate imaging. This research uses a qualitative approach and literature study methodology, namely by looking for various references regarding the image of potential leaders, both from books and scientific journals. Apart from that, political communication strategies that encourage positive differentiation towards political opponents also play an important role in increasing electability. The implications of this research emphasize the importance of coordinating all elements of political communication in order to maximize the effectiveness of a candidate's image. Political communication has an important role in shaping the image strategy of a potential leader in the eyes of the public. Appropriate political branding is aimed at increasing electability through forming positive public opinion towards candidates. This research aims to analyze which message designs and political communication channels are most effective in building a strong reputation and image for a potential leader. A literature study was carried out on several references related to political communication strategies in relation to candidate imaging. This research uses a qualitative approach and literature study methodology, namely by looking for various references regarding the image of potential leaders, both from books and scientific journals. Apart from that, political communication strategies that encourage positive differentiation towards political opponents also play an important role in increasing electability. The implications of this research emphasize the importance of coordinating all elements of political communication in order to maximize the effectiveness of a candidate's image.